Longevity and health: trends in functional limitations and disability among older adults in Portugal, 1985-2005 - Nogueira, D.; Reis, E. (Ageing International, 2014)
This research aimed to analyze trends in functional autonomy of the Portuguese population with 65 years and over, between 1985 and 2005 and find the variables that best explain disability. Data sources comprise the four National Health Surveys (NHS) undertaken so far in Portugal (1987, 1995, 1998, 2005). The study is descriptive and correlational. A regression model was constructed to explain a disability index that was built from the variables related to functional autonomy included in the 2005NHS. There was a negative Compounded Annual Growth Rate (CAGR) between 1987 and 1995NHSs and 1998/2005NHSs (-2.67 %) but between 1995 and 1998 the CAGR was positive (3.12 %). Variables that explain disability were age, sex, education, income, chronic diseases and self-perception of health status.. In the timeframe considered by the NHS authors found no defined trend in the prevalence of disability. The underlying reasons may be related, on the one hand, by the improvements in the living conditions of the Portuguese population from the 80's but, in the other hand, this fact led to a progressive increase of the cohort with 85 years and more, much more vulnerable to chronic diseases.